Trends in the digitalization of the financial sector: the rise of digital assets - Nan, Cheng (KSU Publ., 2020)
With the term of blockchain technology, digital assets as Bitcoin have also instantly developed. In last decades, although the improvement in digital assets has been blocked by some nation’s policy, it is also attractive for many investors in the capital market. This article explains the increasing interests for digital assets.
Keywords: Bitcoin; Blockchain; crypto-currency; trading; digital assets